Evaluation of Elarom SES with or without Tri-basic Copper Chloride on Nursery Pig Growth Performance - H. Williams; J. C. Woodworth; J. M. DeRouchey; S. S. Dritz; M. D. Tokach; R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2017)
A total of 360 weanling pigs (DNA 200 × 400; initially 11.5 lb BW) were used in a 42-d study evaluating the effects of feeding Elarom SES in combination with increasing tri-basic copper chloride on nursery pig performance and fecal consistency. Elarom SES (Trouw Nutrition USA, Highland, IL) is a specialty feed ingredient containing a blend of active ingredients designed to enhance growth performance and gut health. Tri-basic copper chloride (TBCC, Intellibond C, Micronutrients USA, LLC., Indianapolis, IN) is a form of copper (Cu) that has the potential for improved bioavailability and enhanced growth performance. Pigs were weaned at approximately 21 d and allotted to pens based on initial BW in a completely randomized design. Experimental diets were fed in 3 phases (phase 1, d 0 to 7; phase 2, d 7 to 21; and phase 3, d 21 to 42 post-weaning) in meal form. Experimental treatments were arranged as a 2 × 3 factorial with main effects of Elarom SES (none vs. 0.2% in all phases) and TBCC (none, 108, or 183 ppm of Cu in phase 3 only). Fecal consistency was determined by visual appraisal of pen floors on d 0, 4,7, 14, 21, 28, 35, and 42 on a scale from 1-5. A score of 1 indicated hard, pellet type feces and a score of 5 indicated watery, liquid feces. Overall, there was no evidence for treatment differences observed for ADG, ADFI, or fecal consistency; however, a tendency for an Elarom SES × TBCC interaction was observed for F/G (quadratic, P = 0.061). This was the result of F/G improving at the intermediate level of TBCC without Elarom SES, yet F/G was improved at the highest level of TBCC when Elarom SES was present. Overall, no consistent benefit was observed from feeding Elarom SES or different levels of TBCC on growth performance or fecal consistency of weaned pigs.
Keywords: copper; Elarom SES; growth performance; nursery